2006
DOI: 10.3748/wjg.v12.i45.7278
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the severity of hepatitis C virus-related liver disease and the presence ofHelicobacterspecies in the liver: A prospective study

Abstract: Our results do not confirm the association of Helicobacter species DNA in the liver of CHC patients with advanced liver disease. The lack of correlation between positive H pylori serology and the presence of H pylori-like DNA in the liver may indicate the presence of a variant of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
7
18
1
Order By: Relevance
“…Our result were similar to the study of Caste´ra et al (2006) in which observations showed that higher propagation of HP DNA in hepatic specimens from fibrotic and non-fibrotic livers. High participation of Helicobacter pylori DNA in the cases with progressive phase of fibrosis than minimal phase of it may indicate the HP role in the advance of the chronic viral hepatitis toward hepatocellular carcinoma (Caste´ra et al, 2006).…”
Section: Determinantssupporting
confidence: 92%
See 3 more Smart Citations
“…Our result were similar to the study of Caste´ra et al (2006) in which observations showed that higher propagation of HP DNA in hepatic specimens from fibrotic and non-fibrotic livers. High participation of Helicobacter pylori DNA in the cases with progressive phase of fibrosis than minimal phase of it may indicate the HP role in the advance of the chronic viral hepatitis toward hepatocellular carcinoma (Caste´ra et al, 2006).…”
Section: Determinantssupporting
confidence: 92%
“…In this study, DNA of Helicobacter pylori was tested on biopsies of 44.9% hepatitis C virus Egyptian patients, agrees with previous studies (Caste´ra et al, 2006;Rocha et al, 2005 andDore et al, 2002).…”
Section: Determinantssupporting
confidence: 91%
See 2 more Smart Citations
“…The geographical distribution of H. bilis or other enteric Helicobacter species in humans is unknown but suggests that their prevalence may be low in populations at low risk for nonviral hepatitis and biliary duct malignancies (4,5,30,37,38,48) but could contribute to the unexplained increase of extra-and intrahepatic cancer inci- (18,39,44) and the wide geographical variation in the incidence of gallbladder and extrahepatic bile duct cancers observed in other regions (36). Enterohepatic Helicobacter infection could also be a factor in the development of cholesterol gallstones and intrahepatic cholelithiasis, as suggested by recent studies in animal models (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%